La familia contemporánea : relatos de resiliencia y salud mental (2008)
ABSTRACT: Objectives: To study the promotion of mental health at the family core. Methods: The starting point is the classical conception of family, in which the notion of structure plays a central role and it is represented by the concepts of typology and family functioning. We suggest that the concept of family should be extended in the light of the changes it has undergone and of several post-modern approaches. Five hypotheses were postulated to guide the proposed approach. Conclusions: The structural substrate in the conception of family is criticized. Instead, we propose that the family should be thought of as a confi guration, which is in turn assimilated to family resilience. We postulate that it is this assimilation which offers the possibilities for mental health promotion for both the family and each one of its members.